(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
In the era of globalization, foreign language education is no longer limited to the acquisition of grammar rules and vocabulary; it increasingly emphasizes intercultural competence and cultural awareness. English, as a global lingua franca, functions not only as a means of communication but also as a bridge between diverse cultures. Therefore, effective English language teaching requires approaches that integrate linguistic skills with cultural understanding. One promising and culturally responsive method is the use of proverbs in language instruction.